Woodworking : techniques, tools, projects, and everything you need to know - Gilbert, Vicenç; Martín, Frederic A.; Lazcano, Rodrigo (Skyhorse Publishing, 2023)
An essential reference for learning and honing woodworking and carpentry skills is filled with information on materials, metal fittings, adhesives, finishes, machinery, joint techniques, tools, handling of wood, and creating and decorating projects.